Self-concept in normal and criminal male adolescents: A comparative study - Alaee Karahroudy, F; Kiani, M; Izadi, A; Alavi Majd, H (Advances in Nursing & Midwifery, 2010)
Background and aim One of the fundamental concepts in the development of character with especial importance in adolescence is the concept of self. Therefore, self-concept warrants investigation. The aim of this study was to compare the self-concept of normal and criminal adolescents between 12 and 14 at Tehran. Materials and methods In this descriptive-comparative study, 200 adolescents including all available 50 criminals and 150 normal adolescents selected by purposive sampling took part in the study. Governmental schools from selected districts of Tehran and Disciplinary and Education Center were the places of study. A questionnaire in 2 parts, demographics and items related to self-concept derived from Piers-Harris Questionnaire was used for data collection. Although this questionnaire is considered a valid and reliable tool to measure self-concept in children and adolescents, it was validated again with content validity index (90.12) in this study. Data were analyzed by SPSS 11/5. Findings 51.3% of normal adolescents had negative self-concept (31.3%, negative and 20%, very negative) and 48.7% had positive self-concept. In all (100%) criminal adolescents, self-concept was very negative. Therefore, a significant difference was found between self-concept of the two groups (p=0.001). Conclusion In general, normal adolescents had higher self-concept than criminal ones, which may be related to psychological and familial differences in the 2 groups. Keywords: Crime, Self-concept, Adolescents. *Corresponding Author: Fatemeh Alaee Karahroudy .Dept. of Community Health Nursing, Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences and Health Services, Tehran, Iran E-mail: falaei@Yahoo.com